Type I interferon responses are impaired in latently HIV infected cells. Issue 1 (December 2016) - Ranganath, Nischal; Sandstrom, Teslin; Fadel, Saleh; Côté, Sandra; Angel, Jonathan
Abstract Background The latent HIV-1 reservoir represents the primary barrier to the eradication of HIV-1 infection. The design of novel reservoir-clearance strategies, however, is impeded in part by the inability to distinguish latently HIV-infected cells from uninfected cells. Significant impairment of the type I interferon (IFN-I) response is observed during productive HIV-1 infection. Although this remains poorly described in the context of latent HIV-1 infection, presence of potential defects may serve as a novel therapeutic target. Therefore, IFN-I pathways were characterized using two latently HIV-1-infected cell lines, U1 and OM10.1, in comparison to their respective uninfected parental U937 and HL60 cell lines. Findings Constitutive expression and induction of important mediators of IFN-I signaling including IFNα/β cytokines, IFNAR1, MHC-I, ISG15, and PKR were evaluated following exogenous IFNα or poly(I:C) treatment. Differences in basal expression of IFNAR1, MHC-I, and PKR were observed between the latently HIV-1 infected and uninfected cell lines. In parallel, significant impairments in the induction of MHC-I, ISG15 and PKR, as well as secretion of IFNα/β cytokines were observed in response to appropriate exogenous stimulation within the two latently HIV-infected U1 and OM10.1 cells, relative to their HIV-uninfected parental cells. Conclusions In comparison to the HIV-uninfected U937 and HL60 cell lines, widespread defects in IFN-I responsiveness were observed within the latently HIV-infected U1 and OM10.1 cells. These impairments represent novel therapeutic targets, which may be amenable to strategies currently employed in cancer therapy.